2008
DOI: 10.1071/ap07096
|View full text |Cite
|
Sign up to set email alerts
|

The genetic diversity of ampeloviruses in Australian pineapples and their association with mealybug wilt disease

Abstract: Abstract. Pineapple mealybug wilt-associated virus 1 (PMWaV-1), 2 (PMWaV-2) and 3 (PMWaV-3) have been detected in Australian commercial pineapple crops, along with a previously undescribed ampelovirus, for which the name Pineapple mealybug wilt-associated virus 5 (PMWaV-5) is proposed. Partial sequences extending from open reading frame 1b through to the heat shock protein homologue were obtained for PMWaV-1, -3 and -5. Phylogenetic analyses of selected regions of these sequences indicated that PMWaV-5 is a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 24 publications
1
53
0
1
Order By: Relevance
“…Although these unrooted trees are not intended to predict directions of evolution, they do show phylogenetic relationships [33]. Both of these methods gave predictions similar to those of phylogenetic inference (a minimum evolution method), tree puzzle, and Baysian analyses, previously reported for the HEL, RdRp, Hsp70h, and CP regions of other available ampelovirus sequences [2,12,21]. In all of these analyses, two clades were generated in the genus Ampelovirus.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Although these unrooted trees are not intended to predict directions of evolution, they do show phylogenetic relationships [33]. Both of these methods gave predictions similar to those of phylogenetic inference (a minimum evolution method), tree puzzle, and Baysian analyses, previously reported for the HEL, RdRp, Hsp70h, and CP regions of other available ampelovirus sequences [2,12,21]. In all of these analyses, two clades were generated in the genus Ampelovirus.…”
Section: Discussionmentioning
confidence: 94%
“…Although PMWaV-2 has a similarly located 5.3-kDa hydrophobic protein, the identity is less than 13% ( Table 1). The ORF2 of PMWaV-3 and PMWaV-1 both overlap ORF 1b by 17 nucleotides and are both comprised of 51 residues, whereas the closely related PMWaV-5 [2] is composed of 67 residues. ORF 2 of PMWaV-3 and PMWaV-1 lack the 16 residues at the 5 0 -end of ORF2 that are present in PMWaV-5.…”
Section: Genome Organization Of Pmwav-3mentioning
confidence: 99%
See 1 more Smart Citation
“…Esta planta tenía una coloración roja en la parte central de las hojas maduras, mientras que las jóvenes tenían una verde oscura, y en general no mostraban una reducción en el crecimiento ni flacidez. Como ya se mencionó, el marchitamiento asociado al piojo harinoso en (Ma-PHP) es una de las enfermedades más devastadoras de este cultivo a nivel mundial y ha sido relacionado con cinco ampelovirus diferentes (designados como Pineapple mealybug wilt associated virus-1 al 5) (Gambley et al, 2008). Sin embargo, se ha demostrado que los síntomas típicos de la enfermedad sólo se producen cuando ocurren simultáneamente la infección de Pineapple mealybug wilt associated virus-2 y la alimentación de Dysmicoccus brevipes y/o D. neobrevipes (Sether et al, 1998).…”
Section: Discussionunclassified
“…This plant had a reddish coloration in the central part of the mature leaves while young ones had a dark green, and in general did not show a decrease in growth nor flaccidity. As already mentioned, mealybug wilt of pineapple (MWP) is one of the most devastating diseases of this crop worldwide and has been associated with five different ampeloviruses (designated as Pineapple mealybug wilt associated virus-1 to 5) (Gambley et al, 2008). However, it has been shown that the typical symptoms of this disease are only produced when infection simultaneously occurs of Pineapple mealybug wilt associated virus-2 and feeding of Dysmicoccus brevipes and/or D. neobrevipes (Sether et al, 1998).…”
Section: Discussionmentioning
confidence: 99%